INFLUENCE OF TEACHERS’ FAVOURITISM ON PUPILS LEARNING OUTCOME - Hafees Tosin Sulyman; Olamide Temitope Ayodele (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
Influence Teachers favoritism and pupils learning outcome is a crucial issue that needs urgent attention because empirical studies have shown that teachers favouritism can go a long way in influencing pupils learning outcome and holistic development . This study focuses on influence of teachers favouritism on pupils learning outcome in Ilorin south local government area Kwara state. Decriptive survey research design was adopted, simple random sampling technique was adopted to select (5) private schools and (5) public schools to participate in the study. The instrument used was rating scale titled questionnaire on teachers favouritism on pupils learning outcome (QTFPLO) , another instrument used was achievement test titled pupils learning outcome test (PLOT) test retest was used to determine the reliability and index obtained from the instrument were 0.81 and 0.87. Data were analysed using descriptive statistics of frequency counts , percentage and mean for demographic data and research question while inferential statistics of t-test was used to test the hypotheses. The findings revealed that teachers favouritism is high there is no significant influence of the teacher’s favoritism level on pupils learning outcome in Ilorin South Local Government Area of Kwara State (F (1,217) = 1.417, P > 0.05). There was no significant difference in teacher’s favouritism in Ilorin South Local Government Area of Kwara State based on gender (t = -2.245; df = 18; P > 0.05).There was no significant difference in teacher’s favouritism in Ilorin South Local Government Area of Kwara State based on school type (t = -.272; df = 18; P > 0.05). Teachers should ensure that favouritism should be equal among pupils in class and educational settings. It was recommended that the ministers and other concerned agencies should set seminar, conferences on the advantages and disadvantages on the influence of favouritism on pupils learning outcome.